2006
DOI: 10.1016/j.agwat.2005.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Use of saline and non-potable water in the turfgrass industry: Constraints and developments

Abstract: The need for salt-tolerant turfgrasses is ever-increasing. Rapid urban population growth has put enormous pressures on limited freshwater supplies. Many state and local governments have reacted by placing restrictions on the use of potable water for irrigating turfgrass landscapes, instead requiring use of reclaimed, or other secondary saline water sources. In coastal areas, overpumping, and resultant salt water intrusion of coastal wells used for irrigating turfgrass facilities has widely occurred. The nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 42 publications
6
78
0
5
Order By: Relevance
“…On the other hand, Uddin et al (2009) found 50% reduction in growth at salinity level of 39.8dSm -1 , whereas, in our case less than 50% growth reduction occurred even at 45 dSm -1 salinity level. Marcum (2006) also found similar pattern of results on Bermuda grass cultivars. According to their results, salinity ranging from 26 to 40 dS m −1 caused 50% reduction in shoot dry weight, indicating a wide range in salinity tolerance within this species.…”
Section: Dry Weight (G)supporting
confidence: 73%
“…On the other hand, Uddin et al (2009) found 50% reduction in growth at salinity level of 39.8dSm -1 , whereas, in our case less than 50% growth reduction occurred even at 45 dSm -1 salinity level. Marcum (2006) also found similar pattern of results on Bermuda grass cultivars. According to their results, salinity ranging from 26 to 40 dS m −1 caused 50% reduction in shoot dry weight, indicating a wide range in salinity tolerance within this species.…”
Section: Dry Weight (G)supporting
confidence: 73%
“…Rapid urban population growth has put enormous pressures on limited freshwater supplies. As water shortages continue to escalate worldwide, use of saline water for turf landscape irrigation will be increasingly necessary (Marcum 2006). Recently, application of fertilizers for reducing plant growth restrictions under salinity stress conditions and for increasing fertility of saline soils have been considered (Astaraei and Forouzan Ghohar 2000).…”
mentioning
confidence: 99%
“…Turfgrass salt tolerances are generally expressed based on EC of the saturated soil paste extract (e.g., Marcum 2006;Leinauer and Green, 2011), and therefore, the soil salinity in this study was expressed as EC of the saturated paste extract. The loamy sand and loam soils were selected to represent major soil types on which turfgrasses are grown in the semiarid and arid southwestern USA.…”
Section: Methodsmentioning
confidence: 99%